Física do processo de deposição de filmes finos por spin coating - Peixoto, Raul Batista (2021)
In this work, some of the most used techniques for the formation of thin films with focus on the spin coating process will be approached. The physics involved in the process of film formation by spin coating is discussed, presenting the necessary mathematical formulations for the physical description of this process. It can be observed that each of the formulations presents good approximations and lead to a good physical description of the deposition process. The approximations carried out by Meyerhofer that include evaporation in the process fit very well with the typical solutions used, as confirmed by several authors, while the asymptotic formulation used by Cregan and O’Brien corrects the errors obtained by this approximation.